Facile synthesis and characterization of ultrathin δ-MnO2 nanoflakes. Issue 88 (8th December 2017) - Chen, Xiang; Yan, Shaojiu; Wang, Nan; Peng, Sikan; Wang, Chen; Hong, Qihu; Zhang, Xiaoyan; Dai, Shenglong
Abstract : Ultrathin δ-MnO2 nanoflakes were synthesized via a facile route and present excellent specific capacitance and good cycling stability. Abstract : Ultrathin MnO2 with a 2D structure is extremely attractive, especially in the field of energy storage, as its high surface area enables faradaic charge storage and provides short transport paths for electrons and ions. In this paper, we report a facile synthesis of ultrathin δ-MnO2 nanoflakes with wrinkled morphology via the reduction of potassium permanganate by ethanol in an aqueous solution. The obtained δ-MnO2 nanoflakes were potassium manganese oxide hydrate (K-birnessite) with the chemical formula K0.25 MnO2.06 ·0.51H2 O and had a lamellar structure with monoclinic symmetry. The lateral dimensions of the nanoflakes were in the range of 150–200 nm, as determined by transmission electron microscopy (TEM). A further high-resolution-TEM analysis indicated that these nanoflakes were composed of nano-grains with a thickness of 4–5 nm. It is speculated that the nanoflakes assembled from crystal nuclei 4–5 nm in size, corresponding to ∼7 lamellar layers, along the layer directions. As a result, the assembled nanoflakes inherited the ultrathin nature of these crystal nuclei. Cyclic voltammetry measurements demonstrated the excellent electrochemical properties of the nanoflakes, which can potentially serve as supercapacitor electrode materials.